The Loan Repayment of Customer Who Participate in The Dept Suspention Preoject on a Financial Institution During The Outbreak of Coronavirus Disease 2019 - Sridej, Kasima; Charoensettasilp, Sittchai (Journal of Applied Economics and Management Strategy, 2023)
This study aimed to examine, analyze, and test models of personal, socio-economic factors influencing on possibility of intermittent debt payment of customers enrolling in debt moratorium provided by a financial institution during Covid-19 outbreak. Author collected information from research participants – 347 customers of one financial institution-who engages in debt service under loan agreement. The 310 intact information-completed questionnaires were selected. This study employed cross- sectional data collecting method from January-February 2021 and used package software to explore the factor affecting on loan debt payment by using Binary Logistic Regression Analysis. Results revealed that most participants were male, 41.65 years old, married, graduated below a Bachelor's Degree, have used the service of the financial institution for about 8.79 years, have made regular short – term borrowing, average number of their household members was 4.54, average number of workable persons in the family were 4.46 and most of them don’t have regular income, average monthly expenses were 7,883.55 Baht and majority of them bear the burden of debt. For determining the factors affecting on loan debt payment, it found that the factors influencing on possibility of intermittent debt payment in inverse direction were gender, duration of service usage, regular intermediate-term loan, no-income gaining, and no-debt bearing. However, age, married status, education level, regular long-term loan, numbers of household members, and numbers of workable person in family had effect on possibility of intermittent debt payment in same direction at statistically significant level of 0.05.These findings can be applied for other financial institutions that provide debt moratorium policy to be able to analyze the basic and primary characteristics of their customers.